Proceedings of the 3rd Italian-Polish conference on applications of systems theory to economy, management and technology: Białowieża, Poland, May 26-31, 1976 * Optimization and control theory * A survey of some recent applications of the theory of bilinear to the analysis of other classes O:F NONLINEAR SYSTEMS - Gori-Giorgi, Paola; Isidori, Alberto; Ruberti, Antonio (Instytut Badań Systemowych. Polska Akademia Nauk, 1977)
The bilinear models of systems allows a relevant progress with respect to linear time-invanant models, in the wide range of applications. The success of bilinear models is also due to the possibility of developing their theory in a complete manner becouse of the simplicity of the equations (2). Recently some cases were studied which are linear in the state but the control law is more generał than the linear one. Also there were investigated cases in which the system is linear with respect to the input but not to the state, allows to take into consideration that feedback does not maintain the linearity in the state. The purpose of this pa per is to give a survey of the recent results in the above mentioned directions, showing how much these results are connected with those for bilinear systems.
[4], 67-72 stron ; 21 cm
Bibliografia s. 72